Fatty Acid Composition of Certain Oil Seeds from Nigeria: Fatty Acid Composition of some Oil Seed - Ajayi, Ibironke Adetolu; Marchini, Julius Sergio; Dos-Santos, Jose Ernesto; Sakamoto Hotta, Julia Keiko (Biological Sciences - PJSIR, 2014)